2022
DOI: 10.1063/5.0077074
|View full text |Cite
|
Sign up to set email alerts
|

Thickness dependence of spin–orbit torques in Pt/Co structures on epitaxial substrates

Abstract: We investigate the Pt thickness dependence of spin–orbit torques (SOTs) in Co/Pt layers grown on single crystalline SrTiO3 and LaAlO3 and amorphous SiO2 substrates. We measure the SOT-induced effective damping-like fields and spin Hall magnetoresistances of the Co/Pt (tPt) samples, where tPt varies from 0.5 to 5.5 nm. We find that the Co/Pt layers grown on the single crystalline substrates show weaker thickness dependence of the SOT than the samples on the SiO2 substrate, which cannot be explained by the conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…[12][13][14][15][16][17][18][19][20][21] The latter generates a spin density at the NM/FM interfaces with inversion asymmetry. [22][23][24][25][26][27][28][29][30] Both mechanisms induce spin accumulations, which exert spin torques and manipulate the magnetization direction of the FM layer.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14][15][16][17][18][19][20][21] The latter generates a spin density at the NM/FM interfaces with inversion asymmetry. [22][23][24][25][26][27][28][29][30] Both mechanisms induce spin accumulations, which exert spin torques and manipulate the magnetization direction of the FM layer.…”
mentioning
confidence: 99%
“…[12][13][14][15][16][17][18][19][20][21] The latter generates a spin density at the NM/FM interfaces with inversion asymmetry. [22][23][24][25][26][27][28][29][30] Both mechanisms induce spin accumulations, which exert spin torques and manipulate the magnetization direction of the FM layer.Recent studies have revealed another spin current generation mechanism. In the so-called interface-generated spin current, [31][32][33][34][35] the FM/NM interface gives rise to sizable spin currents.…”
mentioning
confidence: 99%